Economic Revitalization Through Mosques: Enhancing Community Well-Being In Indonesia - Maulidizen, Ahmad; Safa'ah, Amriatus; Maghfirah; Johari; Rizapoor, Habiburrahman (International Journal of Islamic Business and Economics (IJIBEC), 2024)
The objective of this research is to explore the revitalizing the economic function of mosques and improving the economic well-being of the ummah in Indonesia. This research employs a literature review methodology with study can be sourced from various outlets, including journals, books, documentation, the internet, and libraries. The data analyzed using the content analysis method, is a descriptive or scientific analysis of the textual information obtained from library sources. This method involves systematically examining and interpreting the content of the documents to extract meaningful insights and information related to the research topic. The findings are Revitalizing the economic function of mosques and improving the economic well-being of the ummah in Indonesia; (1) Observing Potential Areas for Business Development Around the Mosque; (2) Designing an Investment Platform Accessible to Many People; (3) Collecting Capital from Investors; (4) Legal Entity Licensing; (5) Business Premises Preparation and Business Opening; and (5) Routine Evaluation. And the role of the mosque in economic development can be categorized into five clusters; (1) Mosque as a Sales and Distribution Center for Economic Aid Programs; (2) Mosque as a Fund Collector and Congregant Investment Hub for Mosque Economic Activities; (3) Mosque as a Financial Sector; (4) Mosque as a Marketplace for Small and Medium-Sized Micro-Businesses in the Surrounding Area; and (5) Mosque Establishing Autonomous Business Entities. This research contributes significantly to understanding the opportunities and challenges associated with the economic role of mosques in Indonesia. The findings are expected to serve as a foundation for various stakeholders, including the government, religious organizations, and the ummah community, to develop effective strategies for revitalizing the economic function of mosques and improving the economic well-being of the community in Indonesia